2007
DOI: 10.1086/514822
|View full text |Cite
|
Sign up to set email alerts
|

Immune Suppression in Advanced Chronic Fascioliasis: An Experimental Study in a Rat Model

Abstract: Today, fascioliasis is considered to be an important human disease caused by 2 liver fluke species, Fasciola hepatica and Fasciola gigantica (Fasciolidae), infecting the liver of a wide range of mammals [1] that show a marked variability in their immune response against infection [2]. There are several geographic regions that have been reported to be areas of hypoendemicity, mesoendemicity, and hyperendemicity for fascioliasis in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 42 publications
0
64
0
3
Order By: Relevance
“…Present widespread fascioliasis with high pathogenicity in ruminants from Bangladesh is a good indicator for the disease likely to be diagnosed in humans if properly investigated. The higher proportion of F. gigantica-like forms in the country may suggest more severe pathogenic characteristics related to the larger size of F. gigantica if it infects humans (Girones et al 2007;Valero et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present widespread fascioliasis with high pathogenicity in ruminants from Bangladesh is a good indicator for the disease likely to be diagnosed in humans if properly investigated. The higher proportion of F. gigantica-like forms in the country may suggest more severe pathogenic characteristics related to the larger size of F. gigantica if it infects humans (Girones et al 2007;Valero et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Human cases have been increasing in the five continents, including estimates of human infection of up to 17 million people, or even higher depending from the hitherto unknown situations in Asia and Africa (Mas-Coma et al 2009a). This disease has recently proven to have a great morbidity impact throughout the biliary or chronic period of the disease (Valero et al 2003(Valero et al , 2006aGirones et al 2007), and not only due to the pathogenicity of the acute phase as hitherto believed (Chen and Mott, 1990). Clinical studies have shown this disease to be pronouncedly complex, giving rise to progressive general deterioration of the patients, with sequelae sometimes *Corresponding author: Madela.Valero@uv.es Syed Ali Ahasan et al 268 leaving them handicapped and frail, even including fatal cases (Mas-Coma et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, en las TI, debido a la probable infección reciente o cambio de la fase aguda a crónica, el grado de inmunosupresión es menor; mientras que las VI, por su mayor edad, mayor tiempo de enfermedad y resistencia del parásito a ser eliminado con tratamiento farmacológico, se encuentran en fase crónica, en la cual la inmunosupresión es mayor. El efecto inmunosupresor de F. hepatica se explica por los múltiples papeles que juegan los antígenos parasitarios en la evasión e inmunomodulación ejercida por el parásito (Flynn et al, 2010 Gironenes et al, 2007), poniendo de manifiesto diferencias interespecíficas, así como entre infecciones agudas y crónicas. Así, por ejemplo, en ganado vacuno infectado se produce una elevada respuesta a mitógenos con producción de IFN-γ en fases agudas, mientras que en fases crónicas cae tanto la respuesta a mitógenos como la producción de IFN-γ (Clery et al, 1996 En el presente estudio, tal como se esperaba, los animales controles (CNI) no mostraron respuesta proliferativa a los estímulos específicos por carecer de exposición previa, mientras que los animales infectados (TI y VI) mostraron una respuesta muy baja, siendo las TI las que mostraron una respuesta superior.…”
Section: Discussionunclassified
“…Estos resultados concuerdan con otros estudios, donde quedó de manifiesto la producción de IFN-γ típica de la respuesta Th1 durante las primeras semanas de infección (Clery et al, 1996;Tliba et al, 2002a,b); sin embargo, en etapas crónicas esta producción decae hasta extinguirse, evidenciándose el cambio a una respuesta Th2 con elevada expresión de IL-4 (Brown et al, 1994;O'Neill et al, 2000;Gironenes et al, 2007). No obstante, en un estudio en ovejas cola delgada de Indonesia (ITT) resistentes a infección por F. gigantica (Pleasance et al, 2011) y en otro en conejos con alta protección conferidos con una vacuna contra F. hepatica (Espino y Rivera, 2010), se demuestra que una respuesta temprana tipo Th1 o la dominancia de esta está asociada a la protección y resistencia a la infección.…”
Section: Discussionunclassified
“…Well known in the veterinary field, this disease is also of public health impact with human case numbers and endemic areas increasing in five continents (Mas-Coma et al, 2009a). Human fascioliasis is goining importance with the current, improved understanding of its morbidity due to sustained infection (Valero et al, 2003(Valero et al, , 2006Girones et al, 2007). Due to the parasite/snail relationship, the disease is highly dependent on climatic and environmental characteristics (Ollerenshaw and Smith, 1969;Ollerenshaw, 1974), which explains the influence of climate change and anthropogenic modifications of the environment (e.g.…”
Section: Introductionmentioning
confidence: 99%